Spatiotemporal on Built-Up Area and Population towards Urban Sprawl in Malang City using Google Earth Engine - Puspita, Rafika Tri; Ifan Deffinika; Purwanto; Ike Sari Astuti (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Malang City is the second-most populous city in East Java after Surabaya City. In addition, development in Malang City in recent years has also impacted changes in land use and land cover. The methods used in this research are: 1) built-up area index (EBBI, NDBI, and UI) of Malang City from 2019 to 2023; 2) dasymetric density; 3) distance measurement; and 4) gradient direction. The results of the calculation of the built-up area index show that UI has an average kappa accuracy of 0.75, which is higher than the other two indices. In 2019–2020, the built-up area of Malang City decreased, while in 2021–2023,. There was an increase in the built-up area. This condition is caused by large-scale social restrictions that cause a decrease in development in various sectors. The development of urban sprawl in Malang City in 2019–2023 leads to the north, namely in the districts of Lowokwaru and Blimbing. The correlation test shows that the total population variable has a strong correlation with the urban sprawl (density) variable based on five districts in Malang City.